The first experience of using synthetic Antithrombin-III (Athenativ) in cardiosurgical practice - V. Dehtiar; O. Boichenko; V. Zhovnir; N. Chanhli (Ukrainian Journal of Cardiovascular Surgery, 2017)
Nowadays, the main share of heart surgery performed under artificial circulation, accompanied by a violation of hemostasis. Deficit antithrombin III is 0.02–1% of the population. The main clinical manifestation of deficiency of antithrombin III is thrombosis. The work conducted its own study of communication between levels of antithrombin-III and the result of the activated clotting time during cardiopulmonary bypass in cardiac practice.Demonstrated that the quantitative and/or qualitative deficiency of antithrombin-III results in early postoperative complications and disorders in the hemostatic system.During 2016 at the GI «Scientific-Practical Children`s Cardiac Center» an analysis of 11 patients, average age amounted to 50,2±27,2 years. In 5 (45.4%) patients were available concomitant diseases, in 4 (36.4%) patients – infective endocarditis, in 1 (9%) – HCV. The level of antithrombin-III in the study group amounted to 87.5% in patients with existing co-morbidities – 110.4%, indicating a qualitative deficiency of antithrombin-III in patients with concomitant infectious disease. Averages activated coaghulation time in patients formed the study group 352,4±18,6 seconds after the introduction of additional synthetic antithrombin-III under artificial circulation it reached 535±77 s.We recommend using empirical synthetic antithrombin-III cardiac patients with AСT less than 400 seconds for the exclusion of intraoperative complications such as thrombosis.